Bay leaves (Syzygium polyanthum) extract as a repellent of Culex quinquefasciatus - Rian Oktiansyah; Riyanto; Masagus Mhd. Tibrani; Tiara Ulandari (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
The study of bay leaf extract had been done to know its potential as Culex quinquefasciatus repellent. Bay leaf extract has the secondary metabolite compounds, such as terpenoid that is known as repellent of mosquitoes. The aim of this study was to determine the effect of bay leaf extract on Culex quinquefasciatus. The method used in this study was experiment with complete randomized design which was consisted of six treatments and four repetitions. The treatment consisted of control (0%), P1 (10%), P2 (20%), P3 (30%), P4 (40%), and P5 (50%) of bay leaf extract. Data were analyzed by using one-way ANOVA. The results of this study showed the lowest mean of C. quinquefasciatus which repelled was 83% and the highest was 95,5%. Analysis of variance indicated that amount of C. quinquefasciatus which avoided bay leaf extract was significantly different. Based on the result, it can be concluded that bay leaf extract is potential as C. quinquefasciatus repellent.